Making Modules and Workshops on Product Photo Techniques for Optimization Digital marketing in MSMEs assisted by Telkom CDC - Rahmadanti, Adisya Resti; Putri, Sekar Widyasari; Yesa, Caesareano Lafado; Naufal, Hayu Faiz; Alauddin, Fakhri; Akbari, Ryan; Olivia, Tracy; Prayoga, Denise Sinartan; Destiwardhani, Anggun (Abdi Masyarakat, 2025)
Technology development is the key to the success of this era's industry. As the backbone of the country's economic growth, MSME players are required to be able to make creations and innovations in developing their businesses in order to maintain their existence. On the one hand, technological advances will help MSMEs to innovate, but on the other hand, technological advances cause MSMEs to lag behind in running their business, especially in the marketing sector if MSMEs are unable to use this technology. In the midst of the onslaught of technology and trends that are developing at this time, unfortunately not all MSME players can easily get access to learn about technological developments and trends to be applied in their business. Many MSMEs still do not know how to implement existing technology for their business development. Of course this can be a big obstacle for MSME players in the digital business era. For example, MSME players assisted by Telkom CDC (Community Development Center) are trying to switch from conventional marketing to digital marketing with social media and websites, but buyer interest is still very low because the product photos they display are so simple that they look unattractive. In food products, the photos displayed cannot make potential consumers interested in trying (cannot cause impulsive buying). From the existing problems, the purpose of this community service is to empower MSMEs in terms of technology utilization through product photo training. One introduction to digital technology that can be easily implemented to support marketing is through the application of digital marketing tools such as product photos. The result of the training provided is that MSMEs are able to maximize digital marketing carried out through social media, e-commerce and websites with attractive product photos that attract consumers to see social media from MSMEs.